Macroeconomics - Mytrofanova, A. S. (Національний технічний університет "Харківський політехнічний інститут", 2022)
Individual calculation task in «Мacroeconomics» course is a creative, independent, completed, theoretical and practical work of the student on the proposed topics, which is performed on the basis of the principles and methods of macroeconomic analysis. The structure and state of the main markets of national economy, methods of their qualitative and quantitative analysis, investigation of dynamics of macroeconomic indicators of the country, the state of foreign economic activity – these are the main problems studied in the calculation task. The purpose of writing a calculation task is practical implementation of knowledge, skills and abilities acquired during lectures and practical classes, gaining ability to express an opinion independently, based on use of sources on a particular topic. Internal structure of the calculation task is the following: - Title page; - Contents; - Introduction (relevance of the topic, purpose, objectives of the study); - Theoretical consideration of the essence of the problem; causes, types, consequences of the phenomenon under consideration; - Independently conducted analysis of the problem using statistical data on the basis of the principles and methods of macroeconomic analysis. – Recommendations and conclusions summarizing the author's position on the problem; - References. - Appendix (if applicable). The main stages of performing the calculation task are the following: - choosing the topic (variant is chosen corresponding to the number of the student's surname in the journal of the group); - selecting and studying the literary sources, developing the plan; preparing the theoretical questions. - preparing the analysis of statistical data; - preparing the whole text of the calculation task; - defense of the calculation task.
Keywords: methodical recommendations; calculation task; management; macroeconomics; macroeconomic indicators; business